Human Melanoma-Derived Extracellular Vesicles Regulate Dendritic Cell Maturation - Maus, Rachel L. G.; Jakub, James W.; Nevala, Wendy K.; Christensen, Trace A.; Noble-Orcutt, Klara; Sachs, Zohar; Hieken, Tina J.; Markovic, Svetomir N. (Frontiers in Immunology, 2017)
Evolution of melanoma from a primary tumor to widespread metastasis is crucially dependent on lymphatic spread. The mechanisms regulating the initial step in metastatic dissemination via regional lymph nodes remain largely unknown; however, evidence supporting the establishment of a pre-metastatic niche is evolving. We have previously described a dysfunctional immune profile including reduced expression of dendritic cell (DC) maturation markers in the first node draining from the primary tumor, the sentinel lymph node (SLN). Importantly, this phenotype is present prior to evidence of nodal metastasis. Herein, we evaluate melanoma-derived extracellular vesicles (EVs) as potential mediators of the premetastatic niche through cargo-specific polarization of DCs. DCs matured in vitro in the presence of melanoma EVs demonstrated significantly impaired expression of CD83 and CD86 as well as decreased expression of Th1 polarizing chemokines Flt3L and IL15 and migration chemokines MIP-1α and MIP-1β compared to liposome-treated DCs. Profiling of melanoma EV cargo identified shared proteomic and RNA signatures including S100A8 and S100A9 protein cargo, which in vitro compromised DC maturation similar to melanoma EVs. Early evidence demonstrates that similar EVs can be isolated from human afferent lymphatic fluid ex vivo. Taken together, here, we propose melanoma EV cargo as a mechanism by which DC maturation is compromised warranting further study to consider this as a potential mechanism enabled by the primary tumor to establish the premetastatic niche in tumor-draining SLNs of patients.